Implementation of Integrated Problem-Based Learning Model With Ethno Cemistry Sasambo to Improve Chemistry Literation - Mutiah, Mutiah; Andayani , Yayuk; Siahaan, Jackson; Supriadi, Supriadi; Haris, Mukhtar (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
This research aims to increase the chemistry literation of students through the Integrated Problem Based Learning Model with Ethno Chemistry Sasambo in Analytical Chemistry lecture. The subject of this research is all 86 students who are taking the Chemistry Analytical lecture. Meanwhile, the object is chemistry literation in several aspects such as content, context, competition, and attitude and the response of students toward conducting an Integrated Problem-Based Learning model with local culture in the salt production process. The research methodology used in this research is action class research in three cycles. Each cycle consists of planning, observation, and evaluation-reflection. Results of this work gained are: (1) Increase in students' chemistry literation from mid to high category that can be seen as cycle 1 is 62.8 as enough category, cycle 2 is 70.7 as enough category, and cycle three is 76.7 as high category. (2) Students' response shows that 95% of them stated that they are very interested and wanted more and vary integrated of local culture.